Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12885-022-09729-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients with anal cancer treated with conformal radiotherapy—a systematic review

Abstract: Aims Anal cancer is primarily treated using concurrent chemoradiotherapy (CRT), with conformal techniques such as intensity modulated radiotherapy (IMRT) and volumetric arc therapy (VMAT) now being the standard techniques utilised across the world. Despite this, there is still very limited consensus on prognostic factors for outcome following conformal CRT. This systematic review aims to evaluate the existing literature to identify prognostic factors for a variety of oncological outcomes in ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
5
1
Order By: Relevance
“…Already-established prognostic factors for the outcomes in question have been identified through a systematic review of the literature [ 34 ]. Studies published after 2000 which reported on disease-related outcomes and examined prognostic factors in multivariable analysis for overall survival, locoregional control, and freedom from distant metastasis were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…Already-established prognostic factors for the outcomes in question have been identified through a systematic review of the literature [ 34 ]. Studies published after 2000 which reported on disease-related outcomes and examined prognostic factors in multivariable analysis for overall survival, locoregional control, and freedom from distant metastasis were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…Studies about prognostic biomarkers in ASCC are scarce. T stage, N status, and gender have been associated with prognosis in ASCC 28 . HPV16 infection and several clinical factors as neutrophilia or anemia have also been reported as related to OS and/or DFS 14,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…T stage, N status, and gender have been associated with prognosis in ASCC. 28 HPV16 infection and several clinical factors as neutrophilia or anemia have also been reported as related to OS and/or DFS. 14,29,30 Regarding gene-based biomarkers, p53-positive tumors have a shorter DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that are widely known to affect survival are tumor size, nodal metastasis and sex [5]. Additionally, as etiology of anal cancer is closely related with human papilloma virus (HPV) or human immunodeficiency virus (HIV) infection, immunologic factors such as p16 expression, leukocytopenia, neutropenia, and lymphocytosis have been related with improved survival [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%